2014
DOI: 10.1007/s11121-014-0516-9
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Adolescent Effects of a Universal Group Program for the Parenting of Adolescents

Abstract: There is growing support for the large-scale implementation of parenting programs for the prevention of child behavior disorders and child maltreatment in younger children. However, there is only limited evidence on the efficacy of parenting programs in modifying risk and protective factors relating to adolescent behavior problems. This study examined the efficacy of Group Teen Triple P (GTTP), an eight-session parenting program specifically designed for parents of young adolescents. Seventy-two families with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
2
43
3
2
Order By: Relevance
“…The results of another study involving a sample at risk for child maltreatment indicated that mother-adolescent relationship quality was negatively associated with adolescent internalizing and externalizing symptoms (McWey, Claridge, Stevenson-Wojciak, & Lettenberger-Klein, 2015). In an effort to address the need for tailored interventions aimed at decreasing adolescent behavior problems, results of an 8-week study found increases in parent-adolescent relationship quality and lower levels of family conflict at post-test were associated with lower levels of adolescent behavior problems (Chu, Bullen, Farruggia, Dittman, & Sanders, 2015). In an effort to address the need for tailored interventions aimed at decreasing adolescent behavior problems, results of an 8-week study found increases in parent-adolescent relationship quality and lower levels of family conflict at post-test were associated with lower levels of adolescent behavior problems (Chu, Bullen, Farruggia, Dittman, & Sanders, 2015).…”
Section: Parent-adolescent Relationships Among High-risk Familiesmentioning
confidence: 99%
“…The results of another study involving a sample at risk for child maltreatment indicated that mother-adolescent relationship quality was negatively associated with adolescent internalizing and externalizing symptoms (McWey, Claridge, Stevenson-Wojciak, & Lettenberger-Klein, 2015). In an effort to address the need for tailored interventions aimed at decreasing adolescent behavior problems, results of an 8-week study found increases in parent-adolescent relationship quality and lower levels of family conflict at post-test were associated with lower levels of adolescent behavior problems (Chu, Bullen, Farruggia, Dittman, & Sanders, 2015). In an effort to address the need for tailored interventions aimed at decreasing adolescent behavior problems, results of an 8-week study found increases in parent-adolescent relationship quality and lower levels of family conflict at post-test were associated with lower levels of adolescent behavior problems (Chu, Bullen, Farruggia, Dittman, & Sanders, 2015).…”
Section: Parent-adolescent Relationships Among High-risk Familiesmentioning
confidence: 99%
“…Parents’ negative attitudes decreased in all programs, similar to results from earlier studies that noted increased parental satisfaction and efficacy (Moretti & Obsuth, ) and increased parental confidence (Chu et al ., ) directly after the interventions. We also found that decreases in negative attitudes were maintained, or even continued at follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in parents’ emotional outbursts were similar to those found in earlier studies of various dysfunctional parenting behaviors among parents of adolescents (Chu et al ., ; Leijten et al ., ) and parents of younger children (Stattin et al ., ). Positive parenting behaviors (i.e., attempted understanding) increased in all programs (although the change in Active Parenting was noted only at the one‐year follow‐up).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few general population studies of PTP outcomes are available, and they have been brief PTP's (four hours) (Hiscock et al, 2008), or the study focused on the characteristics of participants (Alfredsson & Broberg, 2016). Few such studies have addressed the effect of these universal programs on parental stress levels (Chu, Bullen, Farruggia, Dittman, & Sanders, 2015;Ulfsdotter, Enebrink, & Lindberg, 2014;Zubrick et al, 2005).…”
Section: Introductionmentioning
confidence: 99%